Coping and quality of life of parents of children with achondroplasia—a narrative review - Adedeji, Adekunle; Witt, Stefanie; Innig, Florian; Alves, Inês; Provasi, Chiara; Sessa, Marco; Mohnike, Klaus; Quitmann, Julia (Frontiers in Medicine, 2025)
BackgroundCaring for individuals with a chronic disease imposes a substantial burden on parents, significantly impacting their quality of life. For parents of children with achondroplasia, caregiving has notable implications for coping mechanisms and overall wellbeing. This review summarizes findings on these parents’ coping strategies and quality of life.MethodsA narrative approach was employed to synthesize research on parental outcomes related to caring for a child with achondroplasia. The PRISMA chart flow was utilized to present the article screening strategy and results, following established guidelines for systematic reviews.ResultsThe review reveals a scarcity of studies examining the impact of caring for a child with achondroplasia on parental outcomes, with only two studies meeting the inclusion criteria. These studies suggest that having a child with achondroplasia significantly affects parental coping and quality of life, indicating substantial emotional and social implications. Additionally, no specific tools or measures to assess outcomes for these parents, highlighting a significant gap in research and resources.ConclusionThe parental experience of caring for a child with achondroplasia involves significant emotional and social challenges. Stressors from emotional distress, social isolation, altered family dynamics, and demanding healthcare interactions underscore the need for robust support systems. Addressing the research gaps requires developing and validating specific measures to assess the outcomes for parents of children with achondroplasia accurately. This will encourage further research and guide the development and evaluation of interventions to improve the coping and QoL of parents of children with achondroplasia.